The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/ijerph18147697
|View full text |Cite
|
Sign up to set email alerts
|

Association of IL-10 and TNF-α Polymorphisms with Dental Peri-Implant Disease Risk: A Meta-Analysis, Meta-Regression, and Trial Sequential Analysis

Abstract: Genetic susceptibility has been reported to be an important risk factor for peri-implant disease (PID). The aim of this meta-analysis was to assess the association between TNF-α and IL-10 polymorphisms and PID susceptibility. The Web of Science, Cochrane Library, Scopus, and PubMed/Medline databases were searched for studies published until 12 April 2021. RevMan 5.3, CMA 2.0, SPSS 22.0, and trial sequential analysis software were used. Twelve studies were included in our analysis. The pooled ORs for the associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Several studies have shown that IL-6, IL-10, TNF-α, and TGF-β1 are closely related to the occurrence and development of PID ( 21 ). IL-6 is a pro-inflammatory factor that promotes the growth and differentiation of osteoclast precursors and alveolar bone resorption ( 22 ), and IL-10 is an important regulator of the pro-inflammatory process, downregulating the synthesis of Th1 pro-inflammatory cytokines and preventing the occurrence of excessive inflammation by acting on macrophages ( 23 ). TNF-α can be produced and released by a variety of cells in the body, with monocyte/macrophages being its main source ( 23 ), and it is one of the key cytokines regulating alveolar bone reconstruction ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that IL-6, IL-10, TNF-α, and TGF-β1 are closely related to the occurrence and development of PID ( 21 ). IL-6 is a pro-inflammatory factor that promotes the growth and differentiation of osteoclast precursors and alveolar bone resorption ( 22 ), and IL-10 is an important regulator of the pro-inflammatory process, downregulating the synthesis of Th1 pro-inflammatory cytokines and preventing the occurrence of excessive inflammation by acting on macrophages ( 23 ). TNF-α can be produced and released by a variety of cells in the body, with monocyte/macrophages being its main source ( 23 ), and it is one of the key cytokines regulating alveolar bone reconstruction ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this view, meta-analyses [6][7][8][9][10], reviews [11], and original articles [12,13] demonstrated the role of several polymorphisms in PIDs. Proinflammatory cytokines, such as interleukins (ILs), are important biochemical mediators to control the host response to inflammation and to also stimulate the production and secretion of prostaglandins.…”
Section: Introductionmentioning
confidence: 99%
“…Peri-implantitis can lead to bone loss and finally implant failure [4,5]. Peri-implantitis, marginal bone loss, and implant failure are three outcomes associated with peri-implant diseases (PIDs) [6,7]. PID is a collective term for reversible peri-implant mucositis and irreversible peri-implantitis [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Peri-implantitis (PI) is characterized by the inflammation and destruction of peri-implant bone tissue, leading to implant failure and loss [ 1 ]. Currently, the research mainly focuses on inflammatory mediators, cells, or molecules related to the PI etiopathogenesis, which could serve as molecular markers useful in the early diagnosis, prognosis, and treatment of the disease [ 2 , 3 , 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%